Analysis of the Use of Artificial Intelligence in the Accounting Profession - Febrianti, Arizqi; Rudianti, Walid; Purbandary, Yenny; Ainiyah, Ghonimah Zumroatun; Permatasari, Kartika Dewi (STIE Pelita Nusantara Semarang, 2026)
This study analyzes the use of Artificial Intelligence (AI) in the accounting profession in Banjarnegara Regency, Central Java. Using a qualitative approach, the research focuses on accounting students' perceptions of AI, the challenges and opportunities of integrating AI into accounting, and its impact on the performance of accounting practitioners. Data collection was conducted through in-depth interviews with three accounting students and two accounting practitioners, supplemented by documentation. The findings of the study indicate that: (1) Accounting students have a positive perception of the use of AI in learning and completing accounting tasks; (2) The integration of AI in accounting presents opportunities for work efficiency while also posing challenges in adapting competencies; (3) The utilization of AI enhances the performance and effectiveness of accounting practitioners, although it introduces risks of dependency and data security. This research contributes empirically to the transformation of the accountant's role in the digital era and implies the need for the development of accounting education curricula that integrate AI technology, as well as the enhancement of digital competencies for accounting practitioners.